CALCULATION OF EARTHQUAKE RESISTANT STRUCTURE OF MEDICAL CENTER BUILDING RUMAH SAKIT UMUM DAERAH (RSUD) SOEDARSO PONTIANAK USING PUSHOVER ANALYSIS - Sutiono, Tansetiadi; Budi, Gatot Setya; Herwani, Herwani (Jurnal Teknik Sipil, 2023)
Hospitals are essential in providing health services and must withstand the forces that may occur, even due to an earthquake. RSUD Soedarso is a hospital in Pontianak City that has been around for a long time. However, because it is already quite old, various problems must be addressed. The step taken by the government is to build a new building, namely the Medical Centre and Inpatient Building.The purpose of writing this final project is to evaluate the performance of the earthquake-resistant structure of the Soedarso Hospital Medical Centre building using the pushover analysis method. This method analyses the inelastic behaviour of the system due to the earthquake, where the result is a curve of the relationship between the shear force and the displacement of the roof that occurs. The guidelines for pushover rules used are based on the provisions of ATC-40 and FEMA 356. Further research was carried out on the dilation between the Medical Centre Building and the IRNA Building.The results are that both buildings are still in elastic condition when the performance point is reached. Based on ATC-40 and FEMA 356, the building is classified as in the Immediate Occupancy (IO) performance level, regarding drift ratio and from plastic hinges that occur in column and beam elements. Then the dilatation that arises due to pushover is smaller than the design dilation of 150 mm. Both buildings are protected from potential collisions, which is a relief.